Long Latency Auditory Evoked Potential in Term and Premature Infants - Didoné, Dayane Domeneghini; Garcia, Michele Vargas; da Silveira, Aron Ferreira (International Archives of Otorhinolaryngology, 2014)
Introduction The research in long latency auditory evokes potentials (LLAEP) in newborns is recent because of the cortical structure maturation, but studies note that these potentials may be evidenced at this age and could be considered as indicators of cognitive development.Purpose To research the exogenous potentials in term and premature infants during their first month of life.Materials and Methods The sample consisted of 25 newborns, 15 term and 10 premature infants. The infants with gestational age under 37 weeks were considered premature. To evaluate the cortical potentials, the infants remained in natural sleep. The LLAEPs were researched binaurally, through insertion earphones, with frequent /ba/ and rare /ga/ speech stimuli in the intensity of 80 dB HL (decibel hearing level). The frequent stimuli presented a total of 80% of the presentations, and the rare, 20%. The data were statistically analyzed.Results The average gestational age of the term infants was 38.9 weeks (± 1.3) and for the premature group, 33.9 weeks (± 1.6). It was possible to observe only the potentials P1 and N1 in both groups, but there was no statistically significant difference for the latencies of the components P1 and N1 (p > 0.05) between the groups.Conclusion It was possible to observe the exogenous components P1 and N1 of the cortical potentials in both term and preterm newborns of no more than 1 month of age. However, there was no difference between the groups.
Keywords: evoked potentials auditory; prematurity; newborn